TSPO Ligands Boost Mitochondrial Function and Pregnenolone Synthesis - Lejri, Imane (J Alzheimers Dis, 2019)
Translocator protein 18 kDa (TSPO) is located in the mitochondrial outer membrane and plays an important role in steroidogenesis and cell survival. In the central nervous system (CNS), its expression is upregulated in neuropathologies such as Alzheimer’s disease (AD). Previously, we demonstrated that two new TSPO ligands based on an imidazoquinazolinone termed 2a and 2b, stimulated pregnenolone synthesis and ATP production in vitro. In the present study, we compared their effects to those of TSPO ligands described in the literature (XBD173, SSR-180,575, and Ro5-4864) by profiling the mitochondrial bioenergetic phenotype before and after treatment and investigating the protective effects of these ligands after oxidative injury in a cellular model of AD overexpressing amyloid-β (Aβ). Of note, ATP levels increased with rising pregnenolone levels suggesting that the energetic performance of mitochondria is linked to an increased production of this neurosteroid via TSPO modulation. Our results further demonstrate that the TSPO ligands 2a and 2b exerted neuroprotective effects by improving mitochondrial respiration, reducing reactive oxygen species and thereby decreasing oxidative stress-induced cell death as well as lowering Aβ levels. The compounds 2a and 2b show similar or even better functional effects than those obtained with the reference TSPO ligands XBD173 and SSR-180.575. These findings indicate that the new TSPO ligands modulate mitochondrial bioenergetic phenotype and protect against oxidative injury probably through the de novo synthesis of neurosteroids, suggesting that these compounds could be potential new therapeutic tools for the treatment of neurodegenerative disease.